Struggling Against Global Capitalism: Women’s Fight for Social & Economic Justice in Indonesia - Aminah, Siti; Wibisono, Rizky Bangun; Fikri, Sulthoni (Dirasat: Human and Social Sciences, 2025)
Objectives: This study examines the struggle of women in Indonesia against the inequalities caused by capitalism, in particular will explore the aspect of Gender Pay Gap. The research aims to provide an explanation of the methods employed by women, particularly those working in the manufacturing sector, to achieve economic justice and equality in the face of capitalist forces that lead to job terminations. Additionally, this study reveals the strategies used by workers to attain social and economic justice in their workplaces. Methods: This research employs an exploratory, descriptive, and analytical approach, utilizing qualitative methods. The study focuses on the struggles of female workers in Indonesia, with a specific emphasis on the industrial manufacturing centers in Jakarta and East Java, particularly in the cities of Surabaya and Sidoarjo. Data collection was conducted through interviews, direct observations, and the use of secondary data sources. Results: The research findings indicate that the struggle of female workers to obtain their rights is severely constrained. Female workers face threats when seeking wage increases, making it exceedingly difficult for them to achieve higher wages. The study also highlights that participation in protests by female workers often leads to the risk of job termination without severance pay. The lack of government support for workers’ efforts to secure wage increases is seen as a stance aligning with global capitalism. Simultaneously, feminist politics often fail to adequately represent women within decision-making institutions. The power dynamics necessary to address social and economic inequalities have not been effectively managed by advocates of gender equality and justice. Conclusions: Based on the aforementioned results, this study recommends enhancing government intervention programs to empower female workers in achieving social and economic justice through wage policy reforms.